ANALISIS PEMANFAATAN INSTAGRAM SEBAGAI MEDIUM EDUKASI KEPEMIMPINAN (Studi Kasus pada Akun @pemimpin.indonesia) - Myranda Fae (2023)
This study examines the role of Instagram social media as an educational medium. Researchers focus on the case of the Instagram account @pemimpin.indonesia as one of the digital platforms providing leadership education. Previous studies have explained that Instagram is a social media platform that offers information, marketing, and business opportunities (Isya et al., 2021; Puspitarini & Nuraeni, 2019). In this research, it is assumed that Instagram users can utilize this platform as an educational medium, especially for leadership topics. The study employs a qualitative approach with a case study method to identify the richness of Instagram as an educational medium. Data collection techniques include interviews, observations, and documentation. The research findings show that the Instagram account @pemimpin.indonesia falls into the Medium category according to Kaplan and Haelin's media classification. It provides features that allow the audience to receive timely information and feedback (immediacy), understand education through various forms such as photos and videos (multiple cues), access information in various languages (variety language), and receive personalized messages (personal focus). In the context of the account's management, Instagram does not occupy a high position since face-to-face video call features are not used for communication, which hinders direct feedback from the audience. However, criticisms from experts regarding the Media Richness Theory demonstrate that Instagram can become a rich medium depending on the needs of the managers and users